Association between perioperative intraperitoneal local anaesthetic infusion and long‐term survival and cancer recurrence after colectomy: follow‐up analysis of a previous randomized controlled trial. Issue 5 (23rd February 2020) - MacFater, Wiremu S.; Xia, Weisi; Barazanchi, Ahmed W. H.; MacFater, Hoani S.; Lightfoot, Nicholas; Svirskis, Darren; Kahokehr, Arman A.; Hill, Andrew G.
Abstract: Background: High concentrations of local anaesthetic have an anti‐proliferative effect on colonic cancer in vitro . Intraperitoneal local anaesthetic (IPLA) has shown analgesic benefit and improved recovery in the perioperative setting. The long‐term effects of IPLA in colon cancer resection have not been examined. This study aims to review the survival and oncological outcomes of a previously conducted trial that compared perioperative IPLA with placebo. Methods: Sixty patients underwent colonic resection for benign and malignant disease as part of a double‐blinded, randomized, placebo‐controlled study between September 2008 and November 2009. The IPLA group received instillation of intraperitoneal ropivacaine before dissection followed by a 3‐day infusion. The placebo group was treated identically but with 0.9% saline solution. A follow‐up analysis was conducted to evaluate overall survival, disease‐free survival and recurrence specifically for patients undergoing resection for stages I–III colon cancer. Kaplan–Meier analysis was performed, and the log‐rank test was used to evaluate difference in survival between groups. Results: Thirty‐seven of the 60 patients had stages I–III colon cancer and were included in this analysis. Nineteen patients were in the placebo group. There was no significant difference in overall survival or all‐cause mortality. There was a higher incidence of cancer‐specific mortality in the local anaesthetic group ( P < 0.046). Conclusion: It does not appear that IPLA is associated with a significant survival benefit in patients with colonic malignancy undergoing colectomy. Other studies are needed to analyse the long‐term outcomes. Abstract : Association between perioperative intraperitoneal local anaesthetic infusion and long‐term survival and cancer recurrence after colectomy: follow‐up analysis of a previous randomized controlled trial.